Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Fluoride induced chondrocyte extracellular matrix degradation by inhibition of glycolysis by the PHD2/HIF1α signaling pathway - Yu Gui; Rui Ma; Lan Ma; Tingling Zou; Kaiqiang Zhang; Xiaoying Guo (Environmental Toxicology and Pharmacology, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Perspectives on the role of postbiotics in meat and meat products: Current status and future trends - Du-xin Jin; Gui-peng Zou; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Meat Science, 2026)

Mechanisms of AMF-mediated correlation between nutrient uptake and soil micropatterns in sugar beet plants under rotational and continuous cropping soil environments - Rui Chen; Yonglong Liu; Xinyi Zhang; Gui Geng; Lihua Yu; Yao Xu; Jiahui Liu; Yuguang Wang (Journal of Cleaner Production, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

High-yield synthesis of biomass-derived carbon dots for enhanced taraxacum growth - Guanxiong Liu; Hui Wang; Jiaxin Dong; Yinying He; Rui Wang; Xiangli Li; Dongyue Liu; Jing Duan; Jing Feng; Xiaoyu Lu; Lijuan Gui; Sheng Hou; et al. (Biomass and Bioenergy, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Integrative transcriptomic and physiological analyses uncover mechanisms by which arbuscular mycorrhizal fungi mitigate salt stress in sugar beet - Zeyuan Cui; Xiaodong Li; Pingan Han; Rui Chen; Yinzhuang Dong; Gui Geng; Lihua Yu; Jiahui Liu; Yao Xu; Yuguang Wang (Mycorrhiza, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

LncRNA OLMALINC promotes osteosarcoma progression through USP1-mediated autophagy suppression - Jianping Li; Bo Yu; Zhaowen Xue; Yiping Liang; Shanchuang Chen; Tao Gui; Zitao Liu; Lei Zhang; Rui Peng (Human Cell, 2025)

Effect of 1-nitropyrene exposure on the biological behavior of trophoblast cells - Chuting Wang; Long Zhang; Daidi Gui; Wenjing Zou; Menglei Zhu; Yu Liu; Lei Hua; Changlian Li; Rui Ding (Reproductive Toxicology, 2025)

Metal-organic coordinated self-assembled nanomedicine for enhanced cuproptosis-mediated chemo-photo-chemodynamic synergistic therapy of non-small cell lung cancer - Ru-Gui Liu; Rui-Rui Zhao; Zi-Wei Yu; Feng-Juan Liu; Chun-Zhao Liu; Xiao Wu (Chemical Engineering Journal, 2025)

Fossil wood of Pinus from the Pliocene of western Yunnan, China and its palaeoclimatic implications - Zhi-Hui Song; Zhuo-Er Wang; Rui Cao; Zhao-Shuai Wang; Huai Wang; Gui-Hua Chen; Jing-Yu Wu (Review of Palaeobotany and Palynology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Dual-targeting of PDPN-expressing synovial fibroblasts and macrophages via CLEC-2-engineered exosomes for osteoarthritis therapy - Bo Yu; Rui Peng; Zitao Liu; Shanchuang Chen; Nanjun Xu; Qingjun Yang; Zhengang Zha; Bolai Chen; Tao Jiang; Tao Gui; Songwei Huan (Chemical Engineering Journal, 2025)

Three new isoquinoline alkaloids from the fermentation of Aspergillus sp. 0338 and their anti-MRSA activities - Min Yang; Miao Dong; Qing-Yang Wu; Shui Yao; Gui Pu; Yue-Yu Ma; Rui-Feng Xiong; Qiu-Fen Hu; Fang Wang; Yin-Ke Li (Natural Product Research, 2025)

Late Neogene monsoonal climate in the southeastern margin of the Tibetan Plateau revealed by leaf physiognomy evidence - Zhuo-Er Wang; Gui-Hua Chen; Rui Cao; Zhi-Hui Song; Zhao-Shuai Wang; Huai Wang; Su-Ting Ding; Jing-Yu Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Three-dimensional discrete element simulation on mechanical response and failure characteristics of composite rock under triaxial unloading condition - Sheng-Qi Yang; Yu Song; Shi-Gui Du; Rui Yong; Su-Sheng Wang; Yun-Jin Hu; Jiang Zhao (Computers and Geotechnics, 2024)

Arbuscular Mycorrhizal Fungi Enhance Tolerance to Drought Stress by Altering the Physiological and Biochemical Characteristics of Sugar Beet - Zeyuan Cui; Rui Chen; Tai Li; Bingchen Zou; Gui Geng; Yao Xu; Piergiorgio Stevanato; Lihua Yu; Vadim N. Nurminsky; Jiahui Liu; Yuguang Wang (Sugar Tech, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Carbon, water and energy fluxes of terrestrial ecosystems in China - Gui-Rui Yu; Zhi Chen; Ying-Ping Wang (Agricultural and Forest Meteorology, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Evaluation on 131I production based on molten salt reactor off-gas extraction - Liang Chen; Liao-Yuan He; Bo Zhou; Gui-Feng Zhu; Yu-Han Fan; Hong-Jie Xu; Rui Yan; Yang Zou (Annals of Nuclear Energy, 2024)

Roxarsone biotransformation by a nitroreductase and an acetyltransferase in Pseudomonas chlororaphis, a bacterium isolated from soil - Jie-wen Ma; Gui-wen Liu; Jia-Yu Zhai; Ke-qian Zhao; Ya-qing Wu; Rui-lian Yu; Gong-ren Hu; Yu Yan (Chemosphere, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Experimental and numerical study on axial compressive behaviors of reinforced UHPC-CFST composite columns - Xiao-Long Gao; Shi-Yu Shen; Gui-Xiang Chen; Rui Pang; Min Mao (Engineering Structures, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Geochronological, geochemical, and P–T path constraints on the late Paleoproterozoic continent–continent collision orogeny in the Quruqtagh Block, Tarim Craton - Tao Cui; Shan-Shan Li; Rui-Qing Guo; Germain Bishikwabo; Xiang-Kuan Gong; Gui-Ping Liu; Yu Guo (Arabian Journal of Geosciences, 2022)

Elevated plasma phage load as a marker for intestinal permeability in leukemic patients - Xue-rui Yin; Ping Liu; Xi Xu; Ying Xia; Kai-zhao Huang; Qiong-dan Wang; Mei-mei Lai; Qi-gui Yu; Xiao-qun Zheng (Medical Microbiology and Immunology, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Regional coupled C-N-H2O cycle processes and associated driving mechanisms - Yang Gao; Gui-rui Yu (Science China Earth Sciences, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Structural characterization and immunosuppressive activity of a new pregnane glycoside from Epigynum cochinchinensis - Yu-Ting Shao; Yan Zhao; Hong Zhang; Meng-Jun Jiang; Afsar Khan; Sheng-Bao Cai; Tian-Rui Zhao; Gui-Guang Cheng; Jian-Xin Cao (Natural Product Research, 2019)

Investigating the urbanization process and its impact on vegetation change and urban heat island in Wuhan, China - Xuan Gui; Lunche Wang; Rui Yao; Deqing Yu; Chang’an Li (Environmental Science and Pollution Research, 2019)

Complete mitochondrial genome of a kind of snakehead fish Channa siamensis and its phylogenetic consideration - Rui Li; Gang Wang; Zheng-Yong Wen; Yuan-Chao Zou; Chuan-Jie Qin; Yu Luo; Jun Wang; Gui-Hong Chen (Genes & Genomics, 2019)

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Evaluation of the Use of SCAR Markers for Screening Genetic Diversity of Lentinula edodes Strains - Jing-Yu Liu; Zheng-He Ying; Fang Liu; Xin-Rui Liu; Bao-Gui Xie (Current Microbiology, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

Foliar and soil 15N natural abundances provide field evidence on nitrogen dynamics in temperate and boreal forest ecosystems - Shu-Lan Cheng; Hua-Jun Fang; Gui-Rui Yu; Tian-Hong Zhu; Jiao-Jiao Zheng (Plant and Soil, 2010)

Bioenergy Sustainability in China: Potential and Impacts - Jie Zhuang; Randall W. Gentry; Gui-Rui Yu; Gary S. Sayler; John W. Bickham (Environmental Management, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

13C abundance, water-soluble and microbial biomass carbon as potential indicators of soil organic carbon dynamics in subtropical forests at different successional stages and subject to different nitrogen loads - Hua-Jun Fang; Gui-Rui Yu; Shu-Lan Cheng; Jiang-Ming Mo; Jun-Hua Yan; Shenggong Li (Plant and Soil, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Root water uptake and profile soil water as affected by vertical root distribution - Gui-Rui Yu; Jie Zhuang; Keiichi Nakayama; Yan Jin (Plant Ecology, 2007)

A coupled model of photosynthesis-transpiration based on the stomatal behavior for maize (Zea mays L.) grown in the field - Gui-Rui Yu; Tatsuaki Kobayashi; Jie Zhuang; Qiu-Feng Wang; Le-Qing Qu (Plant and Soil, 2003)

Research progress of socio-economic water cycle in China - Jia Shao-feng; Wang Guo; Zhang Shi-feng; Yu Gui-rui; Wang Jin-xia; Xia Jun (Journal of Geographical Sciences, 2002)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

A proposal for universal formulas for estimating leaf water status of herbaceous and woody plants based on spectral reflectance properties - Gui-Rui Yu; Takuji Miwa; Keiichi Nakayama; Nobuhiro Matsuoka; Hisashi Kon (Plant and Soil, 2000)